2018
DOI: 10.13045/jar.2018.00283
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Acupuncture Needle Force Generation According to Diameter

Abstract: Background: Various factors can alter the efficacy of acupuncture treatment, such as the location of points, manipulations, depth of insertion, needle retention time, and needle type. In this study, the effect of needle diameter on the efficacy of acupuncture treatment was quantitatively evaluated. Methods: Five acupuncture needles of different diameters used in clinical practice were compared. Force on the porcine tissue phantom was measured using a sensor. Lifting-thrusting and twisting-rotating movements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Including the results of this study, the therapeutic effects of acupuncture on DED have been supported by numerous previous studies. [10][11][12][13]23,25,26,[34][35][36][37] However, the detailed mechanisms that can explain how acupuncture improves DED are still unclear. [43] Until now, the proposed mechanisms of acupuncture for DED include promoting tear secretion, providing analgesic effects for neuropathic pain, suppressing inflammatory responses, improving ocular blood flow, and regulating the nervous and immune systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including the results of this study, the therapeutic effects of acupuncture on DED have been supported by numerous previous studies. [10][11][12][13]23,25,26,[34][35][36][37] However, the detailed mechanisms that can explain how acupuncture improves DED are still unclear. [43] Until now, the proposed mechanisms of acupuncture for DED include promoting tear secretion, providing analgesic effects for neuropathic pain, suppressing inflammatory responses, improving ocular blood flow, and regulating the nervous and immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Acupuncture is the most commonly used Korean medical therapy for DED in clinical practice. Prior studies have also consistently demonstrated the efficacy of acupuncture for DED, [10][11][12][13] but these have been mainly published as case reports.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the operation time is the same, the stimulation amount of lifting-thrusting may be greater than that of twirling ( Wang, 2011 ). Moreover, the stimulation amount of lifting-thrusting tends to increase with increasing needle diameter, which is a feature that twirling does not have ( Lee Y. et al, 2018 ). However, due to the increased collagen winding or rupture caused by twirling, more cellular responses and release of active substances may be mediated by this process ( Zhang et al, 2022 ).…”
Section: Stimulation Parameters Of Ma For Selectionmentioning
confidence: 99%
“…Liu et al [33] used a training method of identifying needle manipulation through a back-propagation neural network with acupuncture force data output from a high-precision pressure sensor. There were 4 articles which entailed phantom-based quantitative measurements, and the phantoms used varied (Table 4) [42][43][44][45]. In 3 Korean articles [42][43][44], needle force with respect to amplitude and frequency was measured with a 6-axis force sensor using the lifting-thrusting technique, while needle force with respect to rotation angle and frequency was measured using the twirling technique.…”
Section: Phantom Models For Needling Trainingmentioning
confidence: 99%
“…There were 4 articles which entailed phantom-based quantitative measurements, and the phantoms used varied (Table 4) [42][43][44][45]. In 3 Korean articles [42][43][44], needle force with respect to amplitude and frequency was measured with a 6-axis force sensor using the lifting-thrusting technique, while needle force with respect to rotation angle and frequency was measured using the twirling technique. The variables affecting needle force were needle diameter, amplitude, and frequency for the lifting-thrusting technique, and angle for the twirling technique.…”
Section: Phantom Models For Needling Trainingmentioning
confidence: 99%